The Effect of Ownership Structure and Corporate Debt on Audit Quality: Evidence from Jordan - Alzeaideen, Khaled Abdulwahab; AL-Rawash, Sara Zakaria (International Journal of Economics and Financial Issues, 2018)
This study investigates the effect of different ownership structure - (Concentration, Foreign, and Institutional Ownership) - and corporate debt on audit quality of listed companies in Amman Stock Exchange. The research has four hypotheses. To test each hypothesis; a model was defined based on dependent variables employed to measure Audit Quality. The sample study consists of 132 companies from 2005 to 2016. The analysis of logistic regression was used to investigate the relationship between the audit quality measured based on the audit firms size as a dependent variable, ownership structure and corporate debt as independent variables. The results provide evidence of positive statistically significant relationship between the audit quality and that of companies both with foreign and institutional ownership. Also, the results reveal a positive significant relationship between the corporate debt and audit quality. In addition, ownership concentration was shown to have a positive relationship with quality, that relationship was not significant. These results are consistent with prior empirical studies. Also, These results indicate that foreign and institutional investors tend to hire high quality auditors. This study helps academicians, regulators, investors, and auditors to have insight into the nature of ownership structure and is it possible for companies’ ownership structures and corporate debt to influence audit quality? Keywords: Audit Quality, Corporate Debt, Concentration Ownership, Foreign Ownership, Institutional Ownership. JEL Classifications: G32, M42